Synchronous prostate and rectal adenocarcinomas irradiation utilising volumetric modulated arc therapy - Ng, Sweet Ping (J Med Radiat Sci, 2015)
Cases of synchronous prostate and colorectal adenocarcinomas have been sporadically reported. There are case reports on patients with synchronous prostate and rectal cancers treated with external beam radiotherapy alone or combined with high‐dose rate brachytherapy boost to the prostate. Here, we illustrate a patient with synchronous prostate and rectal cancers treated using the volumetric arc therapy (VMAT) technique. The patient was treated with radical radiotherapy to 50.4 Gy in 28 fractions to the pelvis, incorporating the involved internal iliac node and the prostate. A boost of 24 Gy in 12 fractions was delivered to the prostate only, using VMAT. Treatment‐related toxicities and follow‐up prostate‐specific antigen and carcinoembryonic antigen were collected for data analysis. At 12 months, the patient achieved complete response for both rectal and prostate cancers without significant treatment‐related toxicities.